Platypnea-Orthodeoxia Syndrome: A Rare Cause of Dyspnea - Ribeiro, Joana Freitas; Gorgulho, Cátia; Lopes, Débora; Matos, Ana; França, Luís; Catorze, Nuno (Brazilian Journal of Case Reports, 2025)
Platypnea-Orthodeoxia Syndrome (POS) is a rare and underdiagnosed condition characterized by dyspnea and hypoxia in the upright and sitting positions, which resolve in the supine position. The authors report the case of a 79-year-old woman with progressively worsening dyspnea over three days. In the emergency department, dyspnea and desaturation were observed, requiring increasing oxygen therapy when standing. Laboratory tests, electrocardiogram, and chest computed tomography revealed no abnormalities to explain the condition. Transthoracic and transesophageal echocardiograms identified a right-to-left shunt caused by a large atrial septal aneurysm, which was treated with closure using an Atriasept – CARDIA™ prosthesis. The procedure led to immediate symptom resolution. POS diagnosis is primarily clinical. While cardiac catheterization is the gold standard for diagnosis, echocardiography plays a crucial role in identifying the underlying etiology. Treatment depends on the cause, and this condition is associated with a good prognosis.